X2+2root 2x-6 by splitting the middle term
Answers
Answered by
7
↑ Here is your answer ↓
_____________________________________________________________
_____________________________________________________________
![x^2 + 2 \sqrt 2 x - 6 = 0 x^2 + 2 \sqrt 2 x - 6 = 0](https://tex.z-dn.net/?f=x%5E2+%2B+2+%5Csqrt+2+x+-+6+%3D+0)
{ Sum =
, Product =
}
∴ Required numbers are
and ![-\sqrt 2 -\sqrt 2](https://tex.z-dn.net/?f=-%5Csqrt+2)
![x^2 + 3 \sqrt 2 x - \sqrt 2 x - 6 = 0 x^2 + 3 \sqrt 2 x - \sqrt 2 x - 6 = 0](https://tex.z-dn.net/?f=x%5E2+%2B+3+%5Csqrt+2+x+-+%5Csqrt+2+x+-+6+%3D+0)
![x(x + 3 \sqrt 2) - \sqrt 2 (x + 3 \sqrt 2) x(x + 3 \sqrt 2) - \sqrt 2 (x + 3 \sqrt 2)](https://tex.z-dn.net/?f=x%28x+%2B+3+%5Csqrt+2%29+-+%5Csqrt+2+%28x+%2B+3+%5Csqrt+2%29)
![(x - \sqrt 2)(x+ 3 \sqrt 2) (x - \sqrt 2)(x+ 3 \sqrt 2)](https://tex.z-dn.net/?f=%28x+-+%5Csqrt+2%29%28x%2B+3+%5Csqrt+2%29)
Hence,
![x = \sqrt 2 x = \sqrt 2](https://tex.z-dn.net/?f=x+%3D+%5Csqrt+2)
![x = - 3 \sqrt 2 x = - 3 \sqrt 2](https://tex.z-dn.net/?f=x+%3D+-+3+%5Csqrt+2)
_____________________________________________________________
_____________________________________________________________
{ Sum =
∴ Required numbers are
Hence,
bhupendrameena085:
Thanx bro
Answered by
2
Hey friend, Harish here.
Here is your answer:
Given:
An expression x² + 2√2 x - 6.
To Do:
Factorize the above expression.
Solution:
![x^{2} +2 \sqrt{2}x - 6 x^{2} +2 \sqrt{2}x - 6](https://tex.z-dn.net/?f=+x%5E%7B2%7D+%2B2+%5Csqrt%7B2%7Dx+-+6+)
Here (a + b) = 2 √2 & ab = -6.
Then,
a = -√2 & b = 3√2
⇒![x^{2} - \sqrt{2}x +3 \sqrt{2}x - 6 x^{2} - \sqrt{2}x +3 \sqrt{2}x - 6](https://tex.z-dn.net/?f=+x%5E%7B2%7D+-+%5Csqrt%7B2%7Dx+%2B3+%5Csqrt%7B2%7Dx+-++6++)
⇒![x(x- \sqrt{2})+3 \sqrt{2}(x - \sqrt{2}) x(x- \sqrt{2})+3 \sqrt{2}(x - \sqrt{2})](https://tex.z-dn.net/?f=x%28x-+%5Csqrt%7B2%7D%29%2B3+%5Csqrt%7B2%7D%28x+-+%5Csqrt%7B2%7D%29+)
⇒![(x+3 \sqrt{2}) (x- \sqrt{2}) (x+3 \sqrt{2}) (x- \sqrt{2})](https://tex.z-dn.net/?f=%28x%2B3+%5Csqrt%7B2%7D%29+%28x-+%5Csqrt%7B2%7D%29+)
Hence the expression is factorized using splitting the middle term.
____________________________________________________
Hope my answer is helpful to you.
Here is your answer:
Given:
An expression x² + 2√2 x - 6.
To Do:
Factorize the above expression.
Solution:
Here (a + b) = 2 √2 & ab = -6.
Then,
a = -√2 & b = 3√2
⇒
⇒
⇒
Hence the expression is factorized using splitting the middle term.
____________________________________________________
Hope my answer is helpful to you.
Similar questions
Math,
9 months ago
World Languages,
9 months ago
Computer Science,
9 months ago
Social Sciences,
1 year ago
Physics,
1 year ago